Vertical Rods as a Seismic Reinforcement Technique for Rammed Earth Walls: An Assessment - Q.-B. Bui; T.-T. Bui; R. El-Nabouch; D.-K. Thai (Advances in Civil Engineering)
Rammed earth (RE) is a construction material which is manufactured by compacting soil by layers within a formwork to build a monolithic wall. RE material is the subject of numerous scientific researches during the last decade because of the significant heritage of RE buildings and the sustainable properties of this material: low embodied energy, substantial thermal inertia, and natural regulator of moisture. The seismic performance of RE buildings is an interesting topic which needs to be thoroughly investigated. This paper presents a numerical study which assesses the relevancy of a seismic reinforcement technique for RE walls by using two vertical steel rods installed at two extremities of the walls. The discrete element method (DEM) was used to model unreinforced and reinforced RE walls. These walls were first loaded with a vertical stress on the top to simulate the vertical loads and then submitted to a horizontal loading on the top to simulate the seismic action. Two current cases of RE buildings were investigated: one-storey and two-storey buildings. The results showed that the reinforcement technique enhanced the maximum horizontal force about 25% and 10%, respectively, for the cases of one- and two-storey buildings. Higher effectiveness of this reinforcement technique is expected for RE materials having higher compressive strength, for example, stabilized RE.